IS IT POSSIBLE TO PREDICT TUMOR PROGRESSION THROUGH GENOMIC CHARACTERIZATION OF MONOCLONAL GAMMOPATHY AND SMOLDERING MULTIPLE MYELOMA? - Ugo Testa; Giuseppe Leone; Elvira Pelosi; Germana Castelli; Valerio De Stefano (Mediterranean Journal of Hematology and Infectious Diseases)
The study of monoclonal serum proteins has led to the generation of two major theories: one proposing that individuals who had monoclonal proteins without any symptoms or evidence of end-organ damage have a benign condition; the other one suggesting that some individuals with asymptomatic monoclonal proteins may progress to multiple myeloma and thus are affected by a monoclonal gammopathy of undetermined significance (MGUS). Longitudinal studies of subjects with MGUS have supported the second theory. Subsequent studies have characterized and defined the existence of another precursor of multiple myeloma, smoldering multiple myeloma (SMM), intermediate between MGUS and multiple myeloma. Primary molecular events, chromosome translocations, and chromosome number alterations resulting in hyperploidy, required for multiple myeloma development, are already observed in myeloma precursors. MGUS and SMM are heterogeneous conditions with the presence of tumors with distinct pathogenic phenotypes and clinical outcomes. The identification of MGUS and SMM patients with a molecularly defined high risk of progression to MM offers the unique opportunity of early intervention with a therapeutic approach on a low tumor burden.